The interdisciplinary dimension in the construction of Environmental Education: A proposal for teaching sequence (Research, Society and Development, 2021)
Environmental Education aims to raise environmental awareness and awareness. This socio-educational scenario, therefore, motivates the investigation of implications arising from the relationship between local spatial identities and the process of scientific literacy on Science Teaching, which aims at the construction of scientific thinking, having as its founding principle the construction of preliminary skills and concepts. In the school period of the Early Years of Elementary School. Thus, the objective in this study is to propose a didactic sequence to develop Environmental Education in an interdisciplinary way. This research deals with action research, with a qualitative approach, with the target audience of teachers and students from the sixth and seventh year of a Public School, in the municipality of Santa Maria, Rio Grande do Sul, Brazil. The proposal resulted in an important resource for the teaching and learning processes, as it aimed to articulate the school's curricular knowledge with Environmental Education in a different and exciting way and has the potential to be applied in different school contexts, always keeping in mind that the disciplines are in constant dialogue with other areas of knowledge, and, through concrete actions, student learning is favored.